Carbon thermal reduction-driven high-entropy oxide metastable-state material as well as preparation method and application thereof
The carbon-supported high-entropy oxide metastable material was prepared by carbothermal reduction, which solved the problem of poor electromagnetic response of high-entropy oxides under non-equilibrium conditions and achieved excellent impedance matching and wide electromagnetic absorption bandwidth, making it suitable for industrial electronics, medical communications and military stealth.
Patent Information
- Application Number
- CN202511252660.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-12-12
AI Technical Summary
In the existing technology, the metastable phase formation of high-entropy oxides and the methods for controlling their content have not been systematically developed, resulting in poor electromagnetic response of the absorbing materials under non-equilibrium conditions, which cannot effectively solve the technical requirements of electromagnetic compatibility and military stealth.
A carbon-loaded high-entropy oxide metastable material was prepared by using a carbothermal reduction-driven method. After ultrasonic treatment of carbon materials and metal salt solutions, a strong alkali was added and stirred to form a coprecipitated polymer. Then, additional iron salt and urea were added, and the mixture was freeze-dried and annealed under low oxygen partial pressure. This process formed a two-phase coupled structure of alloy and high-entropy oxide.
The prepared material has excellent impedance matching and wide electromagnetic absorption bandwidth, making it suitable for industrial electronics, medical communications and military stealth applications, and enhancing the polarization loss and absorption performance of electromagnetic waves.
Smart Images

Figure CN121107469A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials technology, specifically relating to carbothermic reduction-driven high-entropy metastable oxide materials, their preparation methods, and applications. Background Technology
[0002] Breakthroughs in communication technology, particularly the continuous expansion of the high-frequency radio spectrum, have brought unprecedented and drastic changes to the electromagnetic environment of human society. The exponential increase in electromagnetic radiation power not only seriously threatens the operational reliability of precision electronic equipment but also poses a risk of potential synergistic damage to biological tissues due to thermal and non-thermal effects. High-entropy oxides, possessing unique entropy-increasing effects and tunable dielectric-magnetic properties, can be widely applied in the electromagnetic compatibility of consumer electronics and communication equipment, as well as in military stealth applications.
[0003] Current research on the steady-state framework of high-entropy oxides for microwave absorption has made some progress in terms of elemental composition optimization, morphology control and dielectric composite material design. However, the decisive role of thermodynamic and kinetic competition in the intrinsic electromagnetic response of microwave absorbing materials under non-equilibrium conditions is still neglected, and the metastable phase formation and content control methods of high-entropy oxides have not yet been systematically developed.
[0004] Therefore, there is an urgent need for a high-entropy oxide with excellent impedance matching and wide electromagnetic absorption bandwidth to solve the above-mentioned technical problems. Summary of the Invention
[0005] This invention provides the following technical solution: a method for preparing carbothermic reduction-driven high-entropy metastable oxide materials, comprising the following steps:
[0006] S1, dissolve carbon material and soluble metal salt separately in solvent and sonicate to obtain metal salt solution and carbon suspension; S2, add metal salt solution to carbon suspension, add strong base and stir to obtain coprecipitated polymer; S3, redisperse coprecipitated polymer in solvent, add additional iron salt and urea and mix and stir, freeze dry mixed solution to obtain precursor powder; S4, perform staged annealing treatment on precursor powder under low oxygen partial pressure to obtain carbon-supported high-entropy oxide metastable material.
[0007] Preferably, in step S1, the carbon material includes: graphene, carbon nanotubes, and mesophase carbon microspheres; the metal salt includes: iron salt, cobalt salt, nickel salt, chromium salt, and manganese salt; and the mass ratio of metal salt to carbon material is 1:0.1 to 1.
[0008] Preferably, in step S2, the strong alkali includes sodium hydroxide and potassium hydroxide.
[0009] Preferably, in step S3, the molar amount of the additional iron salt is 1% to 30% of the molar amount of the metal salt in step S1.
[0010] Preferably, in step S3, the molar ratio of the additional iron salt to urea is 1:10 to 15.
[0011] Preferably, in step S4, the low oxygen partial pressure atmosphere includes argon and nitrogen; the staged annealing treatment includes: a first stage heat treatment at 330℃~380℃ for 0.8~1.2h, with a heating rate of 5~10℃ / min; and a second stage heat treatment at 700℃~900℃ for 1~6h, with a heating rate of 5~10℃ / min.
[0012] The present invention also discloses a carbon-supported high-entropy oxide metastable material, which is prepared by the above-mentioned carbon-carbon thermal reduction driven high-entropy oxide metastable material preparation method. The carbon-supported high-entropy oxide metastable material is a two-phase coupled structure of alloy and high-entropy oxide, and the weight ratio of metastable alloy phase to high-entropy oxide is 5% to 80%.
[0013] Preferably, the metastable alloy phase is a FeNi3 binary alloy.
[0014] Preferably, the high-entropy oxide includes iron, cobalt, nickel, chromium and manganese, and the particle size of the high-entropy oxide particles is 50 nm to 1 μm.
[0015] This invention also provides an application of carbon-loaded high-entropy oxide metastable materials in impedance matching and wide electromagnetic wave absorption bandwidth technologies.
[0016] The beneficial effects of this invention are:
[0017] 1. The high-entropy oxide metastable material prepared by the method of the present invention is a two-phase coupled structure of alloy phase and high-entropy oxide. The heterogeneous interface enhances the polarization loss of electromagnetic waves and has the advantages of excellent impedance matching and wide electromagnetic wave absorption bandwidth. It can be widely used in industrial electronics, medical communications and military stealth fields.
[0018] 2. The carbon-supported high-entropy oxide metastable material of the present invention is a two-phase coupled structure of FeNi3 alloy and high-entropy oxide, with the metastable phase accounting for 5-80% and the presence of heterogeneous interface enhancing polarization loss.
[0019] 3. The impedance matching of the high-entropy oxide metastable carbon surface of the present invention, with a particle size between 50 nm and 1 μm, is enhanced.
[0020] 4. The preparation method of the present invention utilizes carbothermal reduction to drive the entropy forming process of metal elements and the formation of metastable alloy phases, providing a general means for using thermodynamic and kinetic competition to control the intrinsic electromagnetic properties of microwave absorbing materials under non-equilibrium conditions. Attached Figure Description
[0021] Figure 1 This is a scanning electron microscope image of the carbon-supported high-entropy oxide metastable material prepared in Example 1 of the present invention, which is a carbothermal reduction-driven high-entropy oxide metastable material, its preparation method and application.
[0022] Figure 2 This is the X-ray diffraction (XRD) pattern of the carbon-supported high-entropy oxide metastable material prepared in Example 1 of this invention;
[0023] Figure 3 This is a high-resolution electron microscope image of the carbon-supported high-entropy oxide metastable material prepared in Example 1 of this invention;
[0024] Figure 4 This is the energy spectrum of the carbon-supported high-entropy oxide metastable material prepared in Example 1 of this invention;
[0025] Figure 5 This is an electromagnetic absorption loss diagram of the carbon-supported high-entropy oxide metastable material prepared in Example 1 of this invention;
[0026] Figure 6 This is a scanning electron microscope image of the carbon-supported high-entropy oxide metastable material prepared in Example 2 of this invention;
[0027] Figure 7 This is the X-ray diffraction (XRD) pattern of the carbon-supported high-entropy oxide metastable material prepared in Example 2 of this invention;
[0028] Figure 8 This is a high-resolution electron microscope image of the carbon-supported high-entropy oxide metastable material prepared in Example 2 of this invention;
[0029] Figure 9 This is the energy spectrum of the carbon-supported high-entropy oxide metastable material prepared in Example 2 of this invention;
[0030] Figure 10 This is an electromagnetic absorption loss diagram of the carbon-supported high-entropy oxide metastable material prepared in Example 2 of the present invention;
[0031] Figure 11 This is a scanning electron microscope image of the carbon-supported high-entropy oxide metastable material prepared in Example 3 of this invention;
[0032] Figure 12 This is the X-ray diffraction (XRD) pattern of the carbon-supported high-entropy oxide metastable material prepared in Example 3 of this invention;
[0033] Figure 13 This is an electromagnetic absorption loss diagram of the carbon-supported high-entropy oxide metastable material prepared in Example 3 of the present invention;
[0034] Figure 14 This is a scanning electron microscope image of the carbon-supported high-entropy oxide metastable material prepared in Example 4 of this invention;
[0035] Figure 15 This is the X-ray diffraction (XRD) pattern of the carbon-supported high-entropy oxide metastable material prepared in Example 4 of this invention;
[0036] Figure 16 This is an electromagnetic absorption loss diagram of the carbon-supported high-entropy oxide metastable material prepared in Example 4 of this invention;
[0037] Figure 17 This is a scanning electron microscope image of the carbon-supported high-entropy oxide metastable material prepared in Example 5 of this invention;
[0038] Figure 18 This is the X-ray diffraction (XRD) pattern of the carbon-supported high-entropy oxide metastable material prepared in Example 5 of this invention;
[0039] Figure 19 This is an electromagnetic absorption loss diagram of the carbon-supported high-entropy oxide metastable material prepared in Example 5 of the present invention;
[0040] Figure 20 This is the X-ray diffraction (XRD) pattern of the carbon-supported high-entropy oxide steady-state material prepared in Comparative Example 1 of this invention;
[0041] Figure 21 This is an electromagnetic absorption loss diagram of the carbon-loaded high-entropy oxide steady-state material prepared in Comparative Example 1 of this invention. Detailed Implementation
[0042] The related technologies of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0043] like Figures 1-21 As shown, in this embodiment, the method for preparing high-entropy metastable oxides driven by carbothermal reduction includes the following steps:
[0044] S1, carbon materials and metal salts are dissolved in their respective solvents and ultrasonically treated to obtain metal salt solutions and carbon suspensions, respectively. The carbon is treated as follows: carbon serves as a thermal reduction driver for the metastable synthesis of high-entropy oxides. The carbon includes graphene, carbon nanotubes, and mesophase carbon microspheres, preferably graphene. The solvent is any one or more of water, ethanol, methanol, and isopropanol, preferably water. The mass-to-volume ratio of graphene to solvent is (0.25–1.5):1, preferably (0.25–0.75):1, more preferably 0.5:1, in mg / mL. The graphene solution is dispersed using an ultrasonic cell disruptor with an efficiency of 500–1000 W, preferably 500–850 W, more preferably 700 W. The ultrasonic treatment time is between 45–150 min, preferably 60–90 min, more preferably 60 min. The unique cavitation, mechanical, and thermal effects of ultrasound create localized high temperatures and pressures in the solvent, accompanied by a jet, promoting the uniform dispersion of graphene into the solvent to form a graphene suspension. The metal salts are treated as follows: the metal salts are soluble metal salts, specifically including iron, cobalt, nickel, chromium, and manganese salts, preferably ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, chromium chloride hexahydrate, and manganese chloride tetrahydrate. The molar ratio of the soluble metal salts is preferably equimolar, which is beneficial for ensuring the formation of single-phase high-entropy oxides during solid solution treatment. The solvent in this step is the same as the solvent used in the graphene treatment process, preferably water. Ultrasonic dispersion of the metal salt solution is performed using an ultrasonic cleaner. The dispersion time does not need to be too long; it is sufficient to mix the soluble metal salts evenly in the solvent. The ultrasonic time is 3–10 min, preferably 3–5 min, for example, 6 min. The concentration of the corresponding metal ions in each soluble metal salt solution is 0.2–0.8 mol / L, for example, 0.5 mol / L.
[0045] S2, a metal salt solution is added to a carbon suspension, a strong alkali is added and stirred, and a co-precipitated polymer is obtained after pretreatment. In this step, the mass ratio of graphene to metal salt (metal ions) is controlled at (0.11–1):1, preferably (0.15–0.75):1, more preferably 0.36:1. The strong alkali is preferably sodium hydroxide or potassium hydroxide, more preferably sodium hydroxide. When adding sodium hydroxide, the stirring speed is 500–800 r / min, for example 750 r / min, and the stirring time is 0.5–2 h, for example 1 h. The pretreatment step includes centrifugation and washing. The solvent is removed by centrifugation at a speed of 5000–15000 rpm, preferably 5000–10000 rpm, more preferably 10000 rpm; the centrifugation time is 3–8 minutes, preferably 5 minutes. After centrifugation, the product is washed with either deionized water or anhydrous ethanol, preferably deionized water. In this step, the centrifugal washing is performed 3 to 6 times, preferably 5 times. During the washing process, chloride ions and residual sodium hydroxide adsorbed on the graphene surface are washed away. Therefore, the number of washings should not be too few or too many. If the number of washings is too few, the chloride ions on the surface will not be completely washed away, and sodium hydroxide residue will remain, causing the additional iron salt added later to form a precipitate instead of existing in an ionic state. If the number of washings is too many, excess metal ions anchored on the graphene surface will be washed off.
[0046] S3, the co-precipitated polymer is subjected to secondary treatment, redispersed in a solvent, and then treated with additional iron salt and urea to obtain a precursor powder. The solvent in this step is any one or more of water, ethanol, methanol, and isopropanol, preferably water. The molar amount of the additional iron salt (ferric ions) is 1-30% of the metal salt (ferric ion) content in S1. The molar ratio of the additional iron salt (ferric ions) to urea is 1:(10-15), preferably 1:10. The treatment steps include stirring and freeze-drying, specifically as follows:
[0047] (1) Stir the mixture for a long time at a speed of 500r / min to 800r / min, for example 750r / min, for a duration of 1 to 3 hours, for example 2 hours.
[0048] (2) The mixed solution is freeze-dried to obtain precursor powder. The solution needs to be pre-frozen at -40 to -60°C for 24 to 36 hours, preferably at -55°C for 24 hours; the freeze-drying time for the frozen mixed solution is 24 to 72 hours, preferably 25 to 50 hours, and more preferably 36 hours.
[0049] S4. The precursor powder is subjected to staged annealing under low oxygen partial pressure to obtain a carbon-supported high-entropy oxide metastable material. Staged annealing of the precursor powder under low oxygen partial pressure can activate graphene to reduce graphene oxide; simultaneously, five metal hydroxides co-precipitate and pyrolyze into oxides, which then co-melt into high-entropy oxides. Furthermore, due to the thermal reduction ability of carbon, a metastable alloy phase structure is formed during the co-melting of the metal oxides. The low oxygen partial pressure conditions are low-oxygen gases such as argon and nitrogen, preferably argon. The resulting metastable alloy phase is a FeNi3 binary alloy. The staged annealing process includes: a first stage heat treatment at 350℃ for 1 hour, with a heating rate of 5–10℃ / min, preferably 5℃ / min; a second stage heat treatment at 700℃–900℃ for 1–6 hours, with a heating rate of 5–10℃ / min, preferably 700℃ for 2 hours, with a heating rate of 5℃ / min. The ratio of FeNi3 alloy phase to high-entropy oxide varies with different heating temperatures and times. For example, at a heat treatment temperature of 700℃ and a heating time of 1 hour, the ratio of FeNi3 alloy phase to high-entropy oxide is 79.8%:20.2%; at 700℃ and a heating time of 2 hours, the ratio is 61.1%:38.9%; at 900℃ and a heating time of 2 hours, the ratio is 52.2%:47.8%; and at 700℃ and a heating time of 6 hours, the ratio is 34.4%:65.6%. In contrast, heat treatment in a high-oxygen environment (i.e., a first stage of heat treatment at 350℃ for 1 hour in air and a second stage of heat treatment at 700℃ for 2 hours in argon) produces a pure high-entropy oxide product with 0% FeNi3 alloy phase content.
[0050] In addition, this embodiment also provides a carbon-supported high-entropy oxide metastable material, which is prepared by the above-described preparation method. The high-entropy oxide metastable material is a two-phase coupled structure of alloy and high-entropy oxide, and the metastable alloy phase is a FeNi3 binary alloy.
[0051] Furthermore, the high-entropy oxides include iron, cobalt, nickel, manganese, and chromium, derived from soluble metal salts, with the metastable FeNi3 alloy phase comprising 5–80% of the high-entropy oxides.
[0052] Furthermore, the high-entropy oxide particles have a particle size of 50 nm to 1 μm, a minimum reflection loss RLmin of -50.6 dB under normal temperature conditions, and a maximum effective absorption bandwidth (EAB) of 5.6 GHz.
[0053] Furthermore, this embodiment also provides an application of carbon-supported high-entropy oxide metastable materials in the electromagnetic field.
[0054] To facilitate understanding of this embodiment, further explanation and description will be provided below with reference to the accompanying drawings and specific examples. The accompanying drawings do not constitute a limitation on the embodiments of the present invention.
[0055] Example 1
[0056] Weigh 50 mg of graphene and place it in 100 mL of water. Use an ultrasonic cell disruptor at 700 W for 60 minutes to obtain a graphene suspension. Prepare solutions of five metal salts: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride hexahydrate, and manganese chloride tetrahydrate, with a metal cation concentration of 0.5 mol / L. Sonicate each metal salt solution for 6 minutes using an ultrasonic cleaner.
[0057] 1 ml of each metal salt solution was added to a 0.5 mg / mL graphene suspension, with a metal salt to graphene mass ratio of 1:0.36. The metal salt consisted of the total mass of five metal ions (Fe, Co, Ni, Cr, and Mn), with each ion at 0.5 mM, for a total metal salt mass of 140 mg. Excess sodium hydroxide (8 mM) was added to ensure complete hydroxide co-precipitation of the metal ions. The mixture was magnetically stirred for 1 hour at 750 rpm. The mixture was then centrifuged and washed five times to obtain the coprecipitated polymer. The coprecipitate was redispersed in 200 ml of water, and 20% iron salt (0.1 mM) was added dropwise, along with 60 mg of urea, maintaining a molar ratio of 1:10 between the added iron salt and urea. The mixture was then stirred for 2 hours and freeze-dried for 36 hours to obtain a black precursor powder. The precursor powder was placed in a tube furnace under argon atmosphere and subjected to staged annealing under the following conditions to obtain carbon-supported high-entropy oxide metastable materials: The staged annealing process included: a first stage heat treatment at 350°C for 1 hour at a heating rate of 5°C / min; and a second stage heat treatment at 700°C for 2 hours at a heating rate of 5°C / min. The carbon-supported metastable material obtained in Example 1 had an average particle size of 100 nm. Figure 1 As shown, using Figure 2 Quantitative phase analysis by XRD revealed that the ratio of FeNi3 alloy phase to high-entropy oxide was 70%:30%.
[0058] The electromagnetic wave absorption performance of the carbon-loaded high-entropy oxide metastable material was tested as follows: The carbon-loaded high-entropy oxide metastable material was mixed with molten paraffin at a mass ratio of 3:7, and then pressed into a coaxial ring-shaped sample in a mold. The outer diameter of the ring was 7.01 mm and the inner diameter was 3.04 mm. The relative complex permittivity and relative complex permeability of the carbon-loaded high-entropy oxide metastable material were measured in the range of 2-18 GHz using a network vector analyzer. The three-dimensional electromagnetic wave absorption and reflection plot was obtained using the following formula:
[0059]
[0060] In formulas (1) and (2), Z0 is the vacuum characteristic impedance, Z in ε represents the normalized input impedance of the electromagnetic absorbing material. r and μ r Let f represent the relative complex permittivity and relative complex permeability of the material, d represent the thickness of the electromagnetic absorbing material, c represent the speed of light in vacuum, Tanh represent the hyperbolic tangent function, and j represent the imaginary number. The obtained electromagnetic absorption loss and effective bandwidth diagrams are shown below. Figure 5 As shown, the carbon-loaded high-entropy oxide metastable material exhibits excellent electromagnetic wave absorption performance, with a minimum reflection loss RLmin of -50.6 dB and a maximum effective absorption bandwidth (EAB, the effective absorption bandwidth being the band where the reflection loss is less than -10 dB) of 5.6 GHz. This is compared with the electromagnetic wave absorption performance diagram of Example 2 (…). Figure 10 Electromagnetic absorption performance diagram of Example 3 () Figure 13 For comparison, the electromagnetic absorption performance diagram of Example 4 is shown. Figure 16 Electromagnetic absorption performance diagram of Example 5 () Figure 19 Electromagnetic absorption performance diagram of Comparative Example 1 () Figure 21 It was found that Example 1 has the strongest electromagnetic wave absorption and reflection loss, and Example 1 is the optimal example.
[0061] Figure 1 The scanning electron microscope (SEM) image of the carbon-supported high-entropy oxide metastable material shows that the average particle size is 100 nm. Figure 3 To obtain a high-resolution electron microscope image of the prepared carbon-supported high-entropy oxide metastable material, the lattice fringes were characterized. The 0.486 nm lattice fringes represent the (111) crystal plane of the high-entropy oxide crystal, and the 0.250 nm lattice fringes represent the...
[0062] The (110) crystal plane of FeNi3 alloy represents the successful preparation of a coupled coexistence structure of high-entropy oxide and FeNi3 alloy. Figure 4 To obtain the energy spectrum of the metastable carbon-supported high-entropy oxide material, from... Figure 4It can be seen that the metallic elements Fe / Co / Ni / Cr / Mn are uniformly distributed in the crystal, further proving the successful co-fusion of high-entropy oxides. Figure 5 Electromagnetic absorption loss diagram of the prepared carbon-loaded high-entropy oxide metastable material.
[0063] Example 2
[0064] Weigh 50 mg of graphene and place it in 100 mL of water. Use an ultrasonic cell disruptor at 700 W for 60 minutes to obtain a graphene suspension. Prepare solutions of five metal salts: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride hexahydrate, and manganese chloride tetrahydrate, with a metal cation concentration of 0.5 mol / L. Sonicate each metal salt solution for 6 minutes using an ultrasonic cleaner.
[0065] 1 ml of each metal salt solution was added to a 0.5 mg / mL graphene suspension, with a mass ratio of metal salt to graphene of 1:0.36. The metal salt consisted of the total mass of five metal ions (Fe, Co, Ni, Cr, and Mn), with each ion at 0.5 mM, for a total mass of 140 mg. Excess sodium hydroxide (8 mM) was added to ensure complete co-precipitation of the metal ions as hydroxides. The mixture was magnetically stirred for 1 hour at 750 rpm. The mixture was then centrifuged and washed five times to obtain the coprecipitated polymer. The coprecipitate was redispersed in 200 ml of water without adding any iron salt or urea. After stirring for 2 hours, the mixture was freeze-dried for 36 hours to obtain a black precursor powder. The precursor powder was placed in a tube furnace under argon atmosphere and subjected to staged annealing under the following conditions to obtain carbon-supported high-entropy oxide metastable materials: the staged annealing process included: a first stage heat treatment at 350°C for 1 hour at a heating rate of 5°C / min; and a second stage heat treatment at 700°C for 2 hours at a heating rate of 5°C / min. The carbon-supported metastable material obtained in Example 2 had an average particle size of 200 nm. Figure 6 As shown, using Figure 7 Quantitative phase analysis by XRD revealed that the ratio of FeNi3 alloy phase to high-entropy oxide was 61.1%:38.9%.
[0066] The electromagnetic absorption performance of the carbon-loaded high-entropy oxide metastable material was tested according to the procedure in Example 1. The test procedure in Example 2 was the same as that in Example 1.
[0067] Figure 6 The image shows a scanning electron microscope (SEM) image of the prepared carbon-supported high-entropy oxide metastable material, revealing an average particle size of 200 nm. Figure 8The high-resolution electron microscope image of the prepared carbon-supported high-entropy oxide metastable material is shown. The lattice fringes are characterized. The 0.298 nm lattice fringes represent the (220) crystal plane of the high-entropy oxide crystal, and the 0.250 nm lattice fringes represent the (110) crystal plane of the FeNi3 alloy. This demonstrates the successful preparation of the coupled coexistence structure of high-entropy oxide and FeNi3 alloy. Figure 9 To obtain the energy spectrum of the metastable carbon-supported high-entropy oxide material, from... Figure 9 It can be seen that the metallic elements Fe, Co, Ni, Cr, and Mn are uniformly distributed in the crystal. Figure 10 The electromagnetic absorption loss diagram of the carbon-loaded high-entropy oxide metastable material shows that the minimum reflection loss RLmin is -22.9dB and the maximum effective absorption bandwidth is 3.26GHz.
[0068] Example 3
[0069] Weigh 50 mg of graphene and place it in 100 mL of water. Use an ultrasonic cell disruptor at 700 W for 60 minutes to obtain a graphene suspension. Prepare solutions of five metal salts: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride hexahydrate, and manganese chloride tetrahydrate, with a metal cation concentration of 0.5 mol / L. Sonicate each metal salt solution for 6 minutes using an ultrasonic cleaner.
[0070] 1 ml of each metal salt solution was added to a 0.5 mg / mL graphene suspension, with a mass ratio of metal salt to graphene of 1:0.36. The metal salt consisted of the total mass of five metal ions (Fe, Co, Ni, Cr, and Mn), with each ion at 0.5 mM, for a total mass of 140 mg. Excess sodium hydroxide (8 mM) was added to ensure complete co-precipitation of the metal ions as hydroxides. The mixture was magnetically stirred for 1 hour at 750 rpm. The mixture was then centrifuged and washed five times to obtain the coprecipitated polymer. The coprecipitate was redispersed in 200 ml of water without adding any iron salt or urea. After stirring for 2 hours, the mixture was freeze-dried for 36 hours to obtain a black precursor powder. The precursor powder was placed in a tube furnace under argon atmosphere and subjected to staged annealing under the following conditions to obtain carbon-supported high-entropy oxide metastable materials: The staged annealing process included: a first stage heat treatment at 350°C for 1 hour at a heating rate of 5°C / min; and a second stage heat treatment at 700°C for 1 hour at a heating rate of 5°C / min. The carbon-supported metastable material obtained in Example 3 had an average particle size of 50 nm. Figure 11 As shown, using Figure 12 Quantitative phase analysis by XRD revealed that the ratio of FeNi3 alloy phase to high-entropy oxide was 61.1%:38.9%.
[0071] The electromagnetic absorption performance of the carbon-loaded high-entropy oxide metastable material was tested according to the procedure in Example 1. The test procedure in Example 3 was the same as that in Example 1.
[0072] Figure 11 The image shows a scanning electron microscope (SEM) image of the prepared carbon-supported high-entropy oxide metastable material, revealing an average particle size of 50 nm. Figure 13 The electromagnetic absorption loss diagram of the carbon-loaded high-entropy oxide metastable material shows that the minimum reflection loss RLmin is -18.2dB and the maximum effective absorption bandwidth is 1.97GHz.
[0073] Example 4
[0074] Weigh 50 mg of graphene and place it in 100 mL of water. Use an ultrasonic cell disruptor at 700 W for 60 minutes to obtain a graphene suspension. Prepare solutions of five metal salts: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride hexahydrate, and manganese chloride tetrahydrate, with a metal cation concentration of 0.5 mol / L. Sonicate each metal salt solution for 6 minutes using an ultrasonic cleaner.
[0075] 1 ml of each metal salt solution was added to a 0.5 mg / mL graphene suspension, with a mass ratio of metal salt to graphene of 1:0.36. The metal salt consisted of the total mass of five metal ions (Fe, Co, Ni, Cr, and Mn), with each ion at 0.5 mM, for a total mass of 140 mg. Excess sodium hydroxide (8 mM) was added to ensure complete co-precipitation of the metal ions as hydroxides. The mixture was magnetically stirred for 1 hour at 750 rpm. The mixture was then centrifuged and washed five times to obtain the coprecipitated polymer. The coprecipitate was redispersed in 200 ml of water without adding any iron salt or urea. After stirring for 2 hours, the mixture was freeze-dried for 36 hours to obtain a black precursor powder. The precursor powder was placed in a tube furnace under argon atmosphere and subjected to staged annealing under the following conditions to obtain carbon-supported high-entropy oxide metastable materials: the staged annealing process included: a first stage heat treatment at 350°C for 1 hour at a heating rate of 5°C / min; and a second stage heat treatment at 900°C for 2 hours at a heating rate of 5°C / min. The carbon-supported metastable material obtained in Example 4 had a particle size of 1 μm. Figure 14 As shown, using Figure 15 Quantitative phase analysis by XRD revealed that the ratio of FeNi3 alloy phase to high-entropy oxide was 52.2%:47.8%.
[0076] The electromagnetic absorption performance of the carbon-loaded high-entropy oxide metastable material was tested according to the procedure in Example 1. The test procedure in Example 4 was the same as that in Example 1.
[0077] Figure 14 The image shows a scanning electron microscope (SEM) image of the prepared carbon-supported high-entropy oxide metastable material, revealing a particle size of 1 μm. Figure 16 The electromagnetic absorption loss diagram of the carbon-loaded high-entropy oxide metastable material shows that the minimum reflection loss RLmin is -15.5dB and the maximum effective absorption bandwidth is 1.4GHz.
[0078] Example 5
[0079] Weigh 50 mg of graphene and place it in 100 mL of water. Use an ultrasonic cell disruptor at 700 W for 60 minutes to obtain a graphene suspension. Prepare solutions of five metal salts: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride hexahydrate, and manganese chloride tetrahydrate, with a metal cation concentration of 0.5 mol / L. Sonicate each metal salt solution for 6 minutes using an ultrasonic cleaner.
[0080] 1 ml of each metal salt solution was added to a 0.5 mg / mL graphene suspension, with a mass ratio of metal salt to graphene of 1:0.36. The metal salt consisted of the total mass of five metal ions (Fe, Co, Ni, Cr, and Mn), with each ion at 0.5 mM, for a total mass of 140 mg. Excess sodium hydroxide (8 mM) was added to ensure complete co-precipitation of the metal ions as hydroxides. The mixture was magnetically stirred for 1 hour at 750 rpm. The mixture was then centrifuged and washed five times to obtain the coprecipitated polymer. The coprecipitate was redispersed in 200 ml of water without adding any iron salt or urea. After stirring for 2 hours, the mixture was freeze-dried for 36 hours to obtain a black precursor powder. The precursor powder was placed in a tube furnace under argon atmosphere and subjected to staged annealing under the following conditions to obtain carbon-supported high-entropy oxide metastable materials: the staged annealing process included: a first stage heat treatment at 350°C for 1 hour at a heating rate of 5°C / min; and a second stage heat treatment at 700°C for 6 hours at a heating rate of 5°C / min. The carbon-supported metastable material obtained in Example 5 had a particle size of 1 μm. Figure 17 As shown, using Figure 18 Quantitative phase analysis by XRD revealed that the ratio of FeNi3 alloy phase to high-entropy oxide was 34.4%:65.6%.
[0081] The electromagnetic absorption performance of the carbon-loaded high-entropy oxide metastable material was tested according to the procedure in Example 1. The test procedure in Example 4 was the same as that in Example 1.
[0082] Figure 17 The image shows a scanning electron microscope (SEM) image of the prepared carbon-supported high-entropy oxide metastable material, revealing a particle size of 1 μm. Figure 19 The electromagnetic absorption loss diagram of the carbon-loaded high-entropy oxide metastable material shows that the minimum reflection loss RLmin is -16.4dB and the maximum effective absorption bandwidth is 1.3GHz.
[0083] Comparative Example 1
[0084] Weigh 50 mg of graphene and place it in 100 mL of water. Use an ultrasonic cell disruptor at 700 W for 60 minutes to obtain a graphene suspension. Prepare solutions of five metal salts: ferric chloride hexahydrate, cobalt chloride hexahydrate, nickel chloride hexahydrate, copper chloride hexahydrate, and manganese chloride tetrahydrate, with a metal cation concentration of 0.5 mol / L. Sonicate each metal salt solution for 6 minutes using an ultrasonic cleaner.
[0085] 1 ml of each metal salt solution was added to a 0.5 mg / mL graphene suspension, with a mass ratio of metal salt to graphene of 1:0.36. The metal salt consisted of the total mass of five metal ions (Fe, Co, Ni, Cr, and Mn), with each ion at 0.5 mM, for a total mass of 140 mg. Excess sodium hydroxide (8 mM) was added to ensure complete co-precipitation of the metal ions as hydroxides. The mixture was magnetically stirred for 1 hour at 750 rpm. The mixture was then centrifuged and washed five times to obtain the coprecipitated polymer. The coprecipitate was redispersed in 200 ml of water without adding any iron salt or urea. After stirring for 2 hours, the mixture was freeze-dried for 36 hours to obtain a black precursor powder. The precursor powder was placed in a tube furnace and subjected to staged annealing under the following conditions to obtain a metastable carbon-supported high-entropy oxide material: The staged annealing process included: a first stage of heat treatment at 350°C in air for 1 hour at a heating rate of 5°C / min; and a second stage of heat treatment at 700°C in argon for 2 hours at a heating rate of 5°C / min. The XRD pattern of the carbon-supported high-entropy oxide obtained in Example 5 is shown below. Figure 20 As shown, quantitative phase analysis revealed that the FeNi3 alloy phase content was 0%, indicating that the crystals are single-phase high-entropy oxides, and the product is a carbon-supported high-entropy oxide stable material.
[0086] The electromagnetic absorption performance of the carbon-loaded high-entropy oxide steady-state material was tested according to the procedure in Example 1. The test procedure in Example 6 was the same as that in Example 1. Figure 21 The electromagnetic absorption loss diagram of the carbon-loaded high-entropy oxide steady-state material shows that the minimum reflection loss RLmin is -7.7dB and the maximum effective absorption bandwidth is 0GHz.
[0087] In summary, the preparation method of this invention involves adding five metal salt solutions to a carbon suspension, adding a strong alkali and stirring to form a coprecipitated complex. The coprecipitate undergoes secondary processing to obtain a precursor powder, which is then subjected to staged annealing under low oxygen partial pressure conditions to obtain a carbon-supported high-entropy oxide metastable material. The resulting high-entropy oxide metastable material has a two-phase coupled structure of alloy and high-entropy oxide, exhibiting excellent impedance matching and a wide electromagnetic absorption bandwidth, and can be widely used in industrial electronics, medical communications, and military stealth fields.
[0088] It should be emphasized that the above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing high-entropy metastable oxide materials driven by carbothermal reduction, characterized in that, Includes the following steps: S1, dissolve carbon material and soluble metal salt in solvent and sonicate to obtain metal salt solution and carbon suspension respectively; S2, the metal salt solution is added to the carbon suspension, a strong alkali is added and stirred to obtain a coprecipitated polymer; S3, the coprecipitated polymer is redispersed in a solvent, additional iron salt and urea are added and mixed, and the mixed solution is freeze-dried to obtain precursor powder; S4, the precursor powder is subjected to staged annealing under low oxygen partial pressure to obtain a carbon-supported high-entropy oxide metastable material.
2. The method for preparing carbothermic reduction-driven high-entropy metastable oxide materials according to claim 1, characterized in that, In step S1, the carbon material includes: graphene, carbon nanotubes, and mesophase carbon microspheres; The metal salts include: iron salts, cobalt salts, nickel salts, chromium salts, and manganese salts; The mass ratio of the metal salt to the carbon material is 1:0.1 to 1.
3. The method for preparing carbothermic reduction-driven high-entropy metastable oxide materials according to claim 1, characterized in that, In step S2, the strong alkali includes sodium hydroxide and potassium hydroxide.
4. The method for preparing carbothermic reduction-driven high-entropy metastable oxide materials according to claim 1, characterized in that, In step S3, the molar amount of the additional iron salt is 1% to 30% of the molar amount of the metal salt in step S1.
5. The method for preparing carbothermic reduction-driven high-entropy metastable oxide materials according to claim 1, characterized in that, In step S3, the molar ratio of the additional iron salt to urea is 1:10-15.
6. The method for preparing carbothermic reduction-driven high-entropy metastable oxide materials according to claim 1, characterized in that, In step S4, the low oxygen partial pressure atmosphere includes: argon and nitrogen. The staged annealing process includes: a first stage of heat treatment at 330℃~380℃ for 0.8~1.2h, with a heating rate of 5~10℃ / min; and a second stage of heat treatment at 700℃~900℃ for 1~6h, with a heating rate of 5~10℃ / min.
7. A carbon-supported high-entropy oxide metastable material, characterized in that, The carbon-supported high-entropy oxide metastable material is prepared by the method for preparing carbothermic reduction-driven high-entropy oxide metastable material according to any one of claims 1-6. The carbon-supported high-entropy oxide metastable material is a two-phase coupled structure of alloy and high-entropy oxide, and the weight ratio of the metastable alloy phase to the high-entropy oxide is 5% to 80%.
8. The carbon-supported high-entropy oxide metastable material according to claim 7, characterized in that, The metastable alloy phase is a FeNi3 binary alloy.
9. A carbon-supported high-entropy oxide metastable material according to claim 7, characterized in that, The high-entropy oxides include iron, cobalt, nickel, chromium, and manganese, and the particle size of the high-entropy oxide particles is 50 nm to 1 μm.
10. The application of the carbon-loaded high-entropy oxide metastable material as described in any one of claims 7 to 9 in impedance matching and wide electromagnetic wave absorption bandwidth technology.
Citation Information
Cited By
Preparation method of neodymium-doped high-entropy oxide / high-entropy alloy / C dual-core-shell structure microwave absorption composite material
CN121373415A
A preparation method of a neodymium element doped high-entropy oxide / high-entropy alloy / C double-core-shell structure microwave absorption composite material
CN121373415B